Association between anthropometric, biomechanical and strength parameters and throwing velocity in elite water polo players - López-Laval, I.; Sitko, S.; Jaime, C.; Alejandro, L. A.; Rafel, C. S. (Journal of Sports Sciences, 2024)
This study investigated the association between shoulder biomechanics, anthropometric variables and isometric and dynamic forces in the pullover exercise and throwing speed in professional water polo players. 30 elite male players (age: 20 ± 2.7 years; height: 180 ± 5.3 cm, body mass: 80 ± 7.0 kg) from the Spanish top division league were assessed. Bayesian bivariate correlations revealed significant positive correlations with lean mass, trunk length, wingspan, shoulder isometric strength, optimal power load, and pullover from 20% to 80% 1RM and a significant negative correlation with the shoulder internal rotation range of movement. The significance was determined when the percentage of the posterior distribution within the region of practical equivalence (ROPE) was <1%. Predictive projection based on leave-one-out cross-validation identified a submodel with three key predictors: shoulder isometric strength, shoulder internal rotation range of motion, and trunk length. The results suggest that coaches should integrate the identified correlation values related to conditional variables into training programs to optimize the throwing speed. Additionally, they should emphasize the role of key determinants such as lean mass, trunk length, and wingspan in throwing performance. Integrating these findings into training regimens could yield more effective strategies for improving throwing performance.